2020
DOI: 10.1002/ajp.23196
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of fecal microbiota transplantation via oral gavage to safely alter gut microbiome composition in marmosets

Abstract: Disruption of microbial communities within human hosts has been associated with infection, obesity, cognitive decline, cancer risk and frailty, suggesting that microbiome-targeted therapies may be an option for improving healthspan and lifespan. The objectives of this study were to determine the feasibility of delivering fecal microbiota transplants (FMTs) to marmosets via oral gavage and to evaluate if alteration of the gut microbiome post-FMT could be achieved. This was a prospective study of marmosets house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some non-pharmacological studies may prevent dual decline but empirical data are needed, such as transcranial direct current stimulation studies, 27 cognitive training, cognitive stimulation/engagement training, [28][29][30][31][32][33][34] blood pressure management, 35 dietary restriction, weight loss, and increased physical activity. 36,37 45 Preliminary results from the anti-amyloid antibody Lecanemab trial show positive effects on both primary and secondary outcomes of dementia. Whether these drug therapies prevent dual decline during aging remains unknown.…”
Section: Respond To the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Some non-pharmacological studies may prevent dual decline but empirical data are needed, such as transcranial direct current stimulation studies, 27 cognitive training, cognitive stimulation/engagement training, [28][29][30][31][32][33][34] blood pressure management, 35 dietary restriction, weight loss, and increased physical activity. 36,37 45 Preliminary results from the anti-amyloid antibody Lecanemab trial show positive effects on both primary and secondary outcomes of dementia. Whether these drug therapies prevent dual decline during aging remains unknown.…”
Section: Respond To the Problemmentioning
confidence: 99%
“…Understanding biological pathways is key to identifying therapeutic targets. Currently, microbiome‐mediated therapies are being examined for aging and healthspan in marmosets 45 . Preliminary results from the anti‐amyloid antibody Lecanemab trial show positive effects on both primary and secondary outcomes of dementia.…”
Section: What Are the Questions To Be Addressed And What Does The Fie...mentioning
confidence: 99%
“…Although extensive clinical studies have proved the safety of FMT ( Goloshchapov et al., 2019 ; Saha et al., 2021 ), a small number of patients undergoing FMT may suffer from adverse reactions such as abdominal pain, diarrhea ( Michailidis et al., 2021 ), recurrent infection, and even death ( Ser et al., 2021 ). Clinical guidelines are the evidence base for medical practice ( Kondylakis et al., 2020 ), and therefore, are important for guiding research and promotion of FMT ( Haifer et al., 2020 ), operating procedures ( Cammarota et al., 2019 ), and administration routes ( Ross and Reveles, 2020 ; Halaweish et al., 2022 ). At the policy and legislative levels, there is a need for both a flexible regulatory framework to promote the application and research, and traceability of fecal donors to ensure patient safety ( Vyas et al., 2015 ; Cammarota et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also used microflora to treat gut microbiota dysbiosis in perioperative KT recipients [99,100] . Fecal microbiota transplantation has been demonstrated to be feasible and effective in improving intestinal flora's composition and metabolism in animal experiments [101] . DeJong et al [102] pointed out that dietary intervention can increase intestinal microbial diversity and short-chain fatty acids (a microbial metabolite that is beneficial to improving frailty), thus reducing systemic inflammation.…”
Section: Interventionsmentioning
confidence: 99%
“…[ 99 , 100 ] Fecal microbiota transplantation has been demonstrated to be feasible and effective in improving intestinal flora's composition and metabolism in animal experiments. [ 101 ] DeJong et al [ 102 ] pointed out that dietary intervention can increase intestinal microbial diversity and short-chain fatty acids (a microbial metabolite that is beneficial to improving frailty), thus reducing systemic inflammation. This research also suggested that supplementation with microbial metabolites lost in frail patients might be a more effective and safer method than direct microbiota transplantation.…”
Section: Interventionsmentioning
confidence: 99%